Fundamental molecular biology - Allison, Lizabeth Ann (Blackwell Pub, 2007)
More accessible to beginning students in the field than its encyclopedic counterparts, Fundamental Molecular Biology provides a distillation of the essential concepts of molecular biology, and is supported by current examples, experimental evidence, an outstanding art program, multimedia support and a solid pedagogical framework